Artificial intelligence to enhance clinical value across the spectrum of cardiovascular healthcare. (11th January 2023) - Gill, Simrat K; Karwath, Andreas; Uh, Hae-Won; Cardoso, Victor Roth; Gu, Zhujie; Barsky, Andrey; Slater, Luke; Acharjee, Animesh; Duan, Jinming; Dall'Olio, Lorenzo; el Bouhaddani, Said; Chernbumroong, Saisakul; et al.
Graphical Abstract: Graphical Abstract Step-wise workflow to improve the value of artificial intelligence in clinical research. AI, artificial intelligence. Abstract: Artificial intelligence (AI) is increasingly being utilized in healthcare. This article provides clinicians and researchers with a step-wise foundation for high-value AI that can be applied to a variety of different data modalities. The aim is to improve the transparency and application of AI methods, with the potential to benefit patients in routine cardiovascular care. Following a clear research hypothesis, an AI-based workflow begins with data selection and pre-processing prior to analysis, with the type of data (structured, semi-structured, or unstructured) determining what type of pre-processing steps and machine-learning algorithms are required. Algorithmic and data validation should be performed to ensure the robustness of the chosen methodology, followed by an objective evaluation of performance. Seven case studies are provided to highlight the wide variety of data modalities and clinical questions that can benefit from modern AI techniques, with a focus on applying them to cardiovascular disease management. Despite the growing use of AI, further education for healthcare workers, researchers, and the public are needed to aid understanding of how AI works and to close the existing gap in knowledge. In addition, issues regarding data access, sharing, and security must be addressed to ensure full engagement by patients and the public. The application of AI within healthcare provides an opportunity for clinicians to deliver a more personalized approach to medical care by accounting for confounders, interactions, and the rising prevalence of multi-morbidity.